Hypertensive patients’ adherence to pharmacological and non-pharmacological treatment methods, in Turkey - Selçuk, Kevser Tarı; Çevik, Celalettin; Mercan, Yeliz; Koca, Haydar (International Journal Of Community Medicine And Public Health, 2017)
Background: The present study was aimed at determining hypertensive patients’ adherence to pharmacological and non-pharmacological treatment methods and factors affecting their adherence. Methods: This cross-sectional study was conducted with 418 patients aged 18 and over who met the inclusion criteria. Adherence to pharmacological and some non-pharmacological treatment methods is the dependent variable of the study. Data were collected using the personal information form, Morisky medication adherence scale. In the analysis, descriptive statistics, the chi square test, and logistic regression analysis were used. The significance level was accepted as p<0.05. Results: The rate of adherence to the pharmacological treatment was 78.2%. The rates of adherence to smoking cessation, diet and physical activity were 49.0%, 55.7% and 20.6% respectively. Age, employment status and perceived health status were associated with the adherence to smoking cessation; perceived income, resort to complementary alternative treatment methods and having regular controls (check-ups) were related to the adherence to the diet, and gender and perceived economic status were related to the adherence to physical activities (p<0.05). Conclusions: While approximately four out of five patients complied with the pharmacological treatment, rates of adherence to non-pharmacological treatment methods were low. Multidisciplinary intervention programs should be planned in order to regularly monitor patients at family health centers, to assess their adherence to treatment modalities and to promote adherence.